2013
DOI: 10.1007/s11739-013-0966-2
|View full text |Cite
|
Sign up to set email alerts
|

Muscle depletion and the prediction of chemotherapy toxicity

Abstract: [No abstract available

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Several studies showed that the decrease of LBM is associated with higher chemotherapy toxicities, as well as a worse outcome in various cancer type [ 5 , 15 40 ]. Moreover, a muscle wasting without adipose tissue and body weight reduction was observed during anticancer treatment with both chemotherapy and target therapy [ 25 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies showed that the decrease of LBM is associated with higher chemotherapy toxicities, as well as a worse outcome in various cancer type [ 5 , 15 40 ]. Moreover, a muscle wasting without adipose tissue and body weight reduction was observed during anticancer treatment with both chemotherapy and target therapy [ 25 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, our results support literature data showing a relation between sarcopenia and toxicity in cancer patients. In fact, sarcopenia is associated to worse outcome, to higher risk of complication after surgical intervention, to higher mortality and to the risk of developing severe toxicities [ 5 , 13 ]. In particular, adverse events are the major cause of dose reduction, delaying of administration and therapy discontinuation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The allele of caveolin-1 G14713A may be used as an early marker for detection of sarcopenia [27]. resulting in increased toxicity due to higher concentrations and to a reduced drug clearance [28]. An alternative drug is recommended for poor chemotherapy metabolizers and a 50% decrease in starting dose for intermediate metabolizers [29].…”
Section: Diagnostic Criteria Of Sarcopeniamentioning
confidence: 99%